THE CORRELATION BETWEEN STUDENTS’ VOCABULARY MASTERY ON TRANSLATING A FAIRY SONG POEM BY WILLIAM SHAKESPEARE - Haerani, Haerani; Azisah, Riska; Hamid, Sitti Maryam; Natsir, Ratu Yulianti (PROJECT (Professional Journal of English Education), 2024)
The limited vocabulary and lack of word variety in translations cause vocabulary mismatches between students. This research aims to ascertain the relationship between students' vocabulary mastery and their ability to translate Shakespeare's poem entitled A Fairy Song. This research uses quantitative techniques to collect and analyze data. Translation proficiency (Y) is the dependent variable in this investigation, while vocabulary mastery (X) is the independent variable. Random sampling was employed to get the research sample data Universitas Muhammadiyah Makassar students made up the study's population. The study sample consisted of 38 students. The researcher comes to the conclusion that there is a weak association between the two variables based on the Pearson correlation coefficient value of 0.274. This association has a significance value (sig. 2-tailed) of 0.096. This number exceeds the widely accepted statistical significance threshold of 0.05. This suggests that there is no statistically significant relationship between translation and vocabulary skills.